1999
DOI: 10.1111/j.1751-0813.1999.tb12123.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods of detection of Chlamydia psittaci in domesticated and wild birds

Abstract: PCR-dot blot detection of C psittaci in birds appears to be more sensitive than cell culture isolation in this study. C psittaci infection of birds may occur in clinically normal captive birds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 38 publications
1
18
0
2
Order By: Relevance
“…Olsen et al (1998) used PCR to test fecal samples and found 9/312 (2.89%) positive birds in Sweden. McElnea and Cross (1999) also used PCR as one of the methods for C. psittaci detection in domestic and wild birds and observed 16% positive samples among captured birds with no clinical signs of illness, similarly to the present study (16.8%). These findings assure the importance of birds, especially pigeons, as C. psittaci-carriers in Brazil.…”
Section: Discussionsupporting
confidence: 71%
“…Olsen et al (1998) used PCR to test fecal samples and found 9/312 (2.89%) positive birds in Sweden. McElnea and Cross (1999) also used PCR as one of the methods for C. psittaci detection in domestic and wild birds and observed 16% positive samples among captured birds with no clinical signs of illness, similarly to the present study (16.8%). These findings assure the importance of birds, especially pigeons, as C. psittaci-carriers in Brazil.…”
Section: Discussionsupporting
confidence: 71%
“…The major advantage of this study was the use of an internally controlled real-time PCR assay. PCR is a sensitive and specific test compared to enzymelinked immunosorbent assays and tissue culture assays available for C. psittaci detection in birds (7,9). Salinas et al reported one of the largest series on the prevalence of C. psittaci in feral pigeons (10).…”
mentioning
confidence: 99%
“…The vaginal swab samples were inoculated into Vero cells, obtained from the Department of Virology, Faculty of Veterinary Medicine, Cairo University, Egypt, and 6-day-old embryonated chicken eggs, as described previously (McElnea and Cross 1999;Celebi and Seyyal 2006;Anonymous 2008).…”
Section: Isolation In Vero Cell Culture and Embryonated Eggsmentioning
confidence: 99%